Analytic phase-screen model for fast simulation of ionospheric scintillation in GNSS signals - Nunes, Fernando (2018)
We propose a fast technique to simulate the effect of ionospheric scintillation on GNSS signals. The method uses a single-layer phase screen model of the ionosphere with the Huygens-Fresnel integral being determined analytically. The adopted model of the ionosphere assumes an infinite train of plasma bubbles drifting eastward with constant velocity. By modifying the total electron content of the plasma bubbles different values of the scintillation index 4 can be obtained. This model is useful for the simulation of equatorial scintillation scenarios.